2022
DOI: 10.1007/s00415-022-11381-8
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary hyper-reflective ovoid mass-like structures (PHOMS) in AQP4-IgG-positive neuromyelitis optica spectrum disease (NMOSD) and MOG-IgG-associated disease (MOGAD)

Abstract: Background Peripapillary hyperreflective ovoid mass-like structures (PHOMS) have recently been described as new optical coherence tomography (OCT) marker. It is not yet clear whether the occurrence of PHOMS is disease-specific or disease-spanning. PHOMS have been described in 16–18% of patients with multiple sclerosis (MS). Currently, no data on the prevalence of PHOMS in other demyelinating diseases including aquaporine-4-IgG-positive neuromyelitis optica spectrum disease (AQP4 + NMOSD) or myeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In addition to MS, PHOMS also appears in two other demyelinating diseases. Gemert et al ( 14 ) detected PHOMS in 17% of AQP4-IgG-positive neuromyelitis optica spectrum disease patients and 14% of MOG-IgG-associated disease patients, comparable to the prevalence of PHOMS in MS patients. They revealed that the development of PHOMS was not associated with disease duration, disability, or optic nerve axonal degeneration ( 14 ).…”
Section: Phoms and Associated Diseasesmentioning
confidence: 79%
See 3 more Smart Citations
“…In addition to MS, PHOMS also appears in two other demyelinating diseases. Gemert et al ( 14 ) detected PHOMS in 17% of AQP4-IgG-positive neuromyelitis optica spectrum disease patients and 14% of MOG-IgG-associated disease patients, comparable to the prevalence of PHOMS in MS patients. They revealed that the development of PHOMS was not associated with disease duration, disability, or optic nerve axonal degeneration ( 14 ).…”
Section: Phoms and Associated Diseasesmentioning
confidence: 79%
“…Gemert et al ( 14 ) detected PHOMS in 17% of AQP4-IgG-positive neuromyelitis optica spectrum disease patients and 14% of MOG-IgG-associated disease patients, comparable to the prevalence of PHOMS in MS patients. They revealed that the development of PHOMS was not associated with disease duration, disability, or optic nerve axonal degeneration ( 14 ). Recently, Aziria et al ( 11 ) retrospectively analyzed 115 eyes with ON involving multiple different etiologies and reported that PHOMS is not a common structure in ON patients, which support a non-inflammatory mechanism in the formation of PHOMS ( 11 ).…”
Section: Phoms and Associated Diseasesmentioning
confidence: 79%
See 2 more Smart Citations
“…Low-quality spectral-domain OCT data will be excluded from the OCT analysis. We plan to qualitatively explore concomitant OCT findings, including microcystic macular oedema (MMO) or peripapillary hyperreflective ovoid mass-like structures (PHOMS) (71,72).…”
Section: Optical Coherence Tomographymentioning
confidence: 99%